Different Effects of Hylocecarus Polyrhizus and Hylocecarus Undatus Extract on Reducing Total Cholesterol of Male Rattus Norvegicus Wistar Strain - Fahriani, Elviza; Mylano, Tri Adi; Hutapea, Johnson (Newinera Publisher, 2024)
A chronic ailment that is caused by excessive food consumption and a lack of physical activity, obesity is a condition that may be prevented. The tropical dragon fruit can control cholesterol levels, support the immune system, and give a natural colorant for culinary applications. In a true experimental research, sample with rats were fed red and white dragon fruit extracts to determine the amounts of cholesterol in their bodies. Spectrophotometry was used to determine the rats' blood lipid profiles, cholesterol levels, and body weight after they were fed a meal that was high in fat and contained duck egg yolk. For this study, extracts from red and white dragon fruits were administered to male Wistar rats to determine their effects on cholesterol levels. After fourteen days, both groups had a reduction in high cholesterol levels, with group 4 exhibiting the most significant drop in cholesterol levels. Additionally, the extracts decreased the levels of MDA while simultaneously increasing the levels of SOD. The most significant rise was seen in group 4, given white dragon fruit extract at 140 mg/200 gr BW daily. SPSS was utilized to analyze the effects of dragon fruit on blood cholesterol levels in experimental animals, employing the LSD technique and one-way ANOVA.